Enzymes and other Laboratory Tests in Human Pancreatitis - Sakena H. Rashed; Fatima A. Mohammad (College of Education for Pure Sciences, 2012)
Abstract: A clinical study of twenty patients with pancreatitis, aged between (45-68) years, attending Alzahrawi hospital in Mosul city. Each pancreatitis patient was evaluated clinically and laboratory examinations have been done including: (Serum sodium, potassium, magnesium, calcium, albumin, triglycerides (T.G), glucose, urea, total bilirubin, amylase, lactate dehydrogenase (LDH, Aspartate transamines (AST). The analysis of results showed that the levels of Serum Sodium, Calcium, Albumin, Potassium and Magnesium were significantly decreased in pancreatitis patients when compared with control, while T.G, glucose, urea, total bilirubin, LDH, AST and amylase levels were significantly elevated in pancreatitis patients when compared with control.